Design of a beamforming-based antenna for detecting environmental noise in a city framework. (December 2021) - Djungha Okitadiowo, John P.; Lay-Ekuakille, A.; Isernia, T.; Massaro, A.
Abstract: The noise magnitude should be drastically limited in any city whatever its source, namely car/train/aircraft traffic, industrial activities, and leisure. The nose pollution has a significant impact on human activities especially for health. However, the environmental pollution due to noise, in its various types, should be monitored with dedicated instrumentation capable of discriminating the type of noise. The antenna sensor, devoted to detecting the quality and the quantity of noise pollution, can be realized using an array of sensors. We propose a design and a simulation of a beamforming-based antenna sensor to detect the direction of arrival (DOA) of noise.